Chronic Febrile Abdominal Algic Syndrome with Respiratory Compromise; in a 57-year-old female patient. About a case (Research, Society and Development, 2023)
Introduction: Acute pancreatitis is an inflammatory disease of the pancreas that is very common in women and is the main cause of hospital admissions manifested by the presence of acute and intense pain in the epigastrium that can radiate in a band toward the flanks.Nosocomial pneumonia is a frequent acute infection in hospitalized patients who did not present symptoms at the time of hospital admission, which can be caused by endogenous or exogenous germs such as: Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus. General Objective: Present the clinical case of a 57-year-old female patient with abdominal pain. fever, nausea and vomiting, compatible with severe acute pancreatitis of biliary origin, cholelithiasis, choledocholithiasis, chronic cholecystitis, mild hepatic steatosis and nosocomial pneumonia. Conclusions: The diagnosis of hypoglycemia due to severe acute pancreatitis of biliary origin, cholelithiasis, choledocholithiasis, chronic cholecystitis, mild hepatic steatosis, and nosocomial pneumonia was established through laboratory and imaging tests.